Investigating Women's Language Features in ‘The Poppy War’ by R.F. Kuang - Adara, Reza Anggriyashati; Victorynie, Irnie; Hamer, Welliam; Lely, Ledy Nur; Cahyati, Ayu Tri (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2025)
Abstract. Investigating women's language features in novels offers insights into their portrayal in fiction. The purpose of this study is to investigate language features by the female main character in the novel The Poppy War by R.F Kuang. This study used Lakoff’s (1975) theory to analyze the dialogues used by the main character. This study applied a descriptive qualitative research design to collect and analyze data. The results of this study suggest that the main character mainly used hedges, tag question, rising intonation, intensifier, hypercorrect grammar, super-polite forms, avoidance of strong swear words, and emphatic stress as the language features. However, the results indicate the lack of use precise color terms and empty adjectives in the dialogues used by the main character of R.F Kuang’s The Poppy War. This study concludes that the dominant use of hedges and fillers suggests the main female character often mitigates her statements, reflecting uncertainty. In contrast, the lack of use of empty adjectives and precise color terms indicate that the female main character tends to focus on actions or strategies instead of showing emotional descriptions or visual details in their language features. The findings of this study indicate the perceptions of modern people to women from ancient era, adding to the insights to language features used by women. These findings can be valuable for both teachers and researchers who analyze the women’s language features in fiction.Keywords: Women Language Features, Fiction, Sociolinguistics